PENGARUH KEMUDAHAN PENGGUNAAN DAN RISIKO TERHADAP MINAT MENGGUNAKAN LAYANAN MOBILE BANKING - Ahsyar, Efan Tri (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
Public interest in using mobile banking services is influenced by various factors, including ease of use and risk. This study aims to analyze the influence of ease of use and risk on the interest in using mobile banking services among customers of BRI Bank Kota Manna Branch, South Bengkulu Regency. The research method is quantitative with a survey approach. The population of the study consists of all customers of BRI Bank Kota Manna Branch, South Bengkulu Regency. The sample size is 77 respondents. Data were collected through questionnaires distributed to customers and then analyzed using multiple linear regression techniques. The results showed that ease of use has a positive and significant influence on the interest in using mobile banking services. This means that the easier the mobile banking service is to use, the higher the customers' interest in using it. Meanwhile, risk has a negative and significant influence on the interest in using mobile banking services, indicating that the higher the perceived risk, the lower the customers' interest in using the service. This study confirms that to increase interest in using mobile banking services, BRI Bank needs to ensure ease of access and use while minimizing risks by enhancing system security and educating customers about data protection and digital transactions. Keywords: Ease of Use, Risk, Interest in Using